1949
DOI: 10.1242/jeb.26.3.304
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Patterns of the Mammalian Testis and Their Functional Significance

Abstract: The testicular artery in mammals convolutes to a variable extent before reaching the testis, and is closely surrounded by the veins of the pampiniform plexus. Evidence is presented suggesting that this vascular mechanism has a thermoregulatory function for the testis. Species differences in the degree of convolution and calibre of the testicular artery and its relation to the veins of the pampiniform plexus would appear to account in some measure for observed differences in abdomino-testicular t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1951
1951
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The mammalian testicular artery is winding and surrounded by the pampiniform plexus. This characteristic structure helps keep the testicular temperature lower than the body temperature (Harrison and Weiner 1949). However, it is unclear by what mechanisms the testis artery winds and the veins surround the artery during the development.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian testicular artery is winding and surrounded by the pampiniform plexus. This characteristic structure helps keep the testicular temperature lower than the body temperature (Harrison and Weiner 1949). However, it is unclear by what mechanisms the testis artery winds and the veins surround the artery during the development.…”
Section: Discussionmentioning
confidence: 99%
“…More studies are required to validate the capability of MRI series in examining the testicular tissue architecture. The vascularity pattern of testis had species variations of lengths of spermatic cord as well as the size and position of the testicles ( 31 ). This study, and that recorded before ( 32 ), confirmed the origin of the testicular artery in camel from the ventral or ventrolateral aspect of the abdominal aorta.…”
Section: Discussionmentioning
confidence: 99%
“…Similar explanations were given by Hofmann ( 34 ) and Hess et al ( 35 ) in cattle bull, Osman et al ( 33 ) in camel, and Elgaafary et al ( 36 ) in the buffalo bull. The degree of arterial convolution in the spermatic cord is directly proportional to the size of the testis which explains the less tortuosity in rodents, carnivores, and human which all have the small sized gonads, and mostly straight testicular artery ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bulls (up to 130 loops), rams (80 loops), and bucks (50 loops) all have a lot of coiling in their testicular artery. In other animal species such as stallions, camels, and dogs, the coiling is comparatively smaller (less than 25 loops), whereas humans have no coiling in the testicular artery (Harrison and Weiner 1949 ; Setchell 1978 ; Gouletsou 2017 ). Variations among animal species in the degree of convolutions of the testicular artery might be attributed to the differences in abdominal–testicular temperature gradients (Harrison and Weiner 1949 ).…”
Section: Anatomical Consideration Of the Testicular Arterymentioning
confidence: 99%
“…On the ventral aspect of the testis, small arterial branches run on the lateral and medial testicular surfaces toward the epididymal edge, until they penetrate the tunica albuginea toward the testicular parenchyma as centripetal arteries (Jantosovicová and Jantosovic 1983 ). In dogs, the convoluted part (named the STA) of the testicular artery is cranial to the testis, while the MTA runs in a straight plane to the caudal pole of the testis, and gives off many branches on either side, from which terminal vessels pass into the testicular parenchyma and directed towards the center of the testis (Harrison and Weiner 1949 ). The proximal portion of the STA (cranial segment of the STA) is loosely convoluted, while the distal portion (looping segment of the STA) is of high convolutions as the artery approached the cranial pole of the testis (Harrison and Weiner 1949 ).…”
Section: Anatomical Consideration Of the Testicular Arterymentioning
confidence: 99%